Effects of gestational thiamine-deprivation and/or exposure to ethanol on crucial offspring rat brain enzyme activities. (3rd August 2021) - Stolakis, Vasileios; Liapi, Charis; Al-Humadi, Hussam; Kalafatakis, Konstantinos; Gkanti, Vasiliki; Bimpis, Alexios; Skandali, Nikolina; Tsela, Smaragda; Theocharis, Stamatios; Zarros, Apostolos; Tsakiris, Stylianos
Abstract: Objective: The fetal alcohol spectrum disorder (FASD) is a group of clinical conditions associated with the in utero exposure to ethanol (EtOH). We have recently examined the effects of a moderate maternal exposure to EtOH on crucial brain enzyme activities in offspring rats, and discussed the translational challenges arising when attempting to simulate any of the clinical conditions associated with FASD. Materials and methods: In this current study, we: (i) address the need for a more consistent and reliable in vivo experimental platform that could simulate milder cases of FASD complicated by simultaneous thiamine-deprivation during gestation and (ii) explore the effects of such a moderate maternal exposure pattern to EtOH and a thiamine-deficient diet (TDD) on crucial enzyme activities in the offspring rat brains. Results: We demonstrate a significant decrease in the newborn and 21-day-old offspring body and brain weight due to maternal dietary thiamine-deprivation, as well as evidence of crucial brain enzyme activity alterations that in some cases are present in the offspring rat brains long after birth (and the end of the maternal exposure to both EtOH and TDD). Conclusions: Our findings provide a preliminary characterization of important neurochemical effects due to maternal exposure to EtOH and TDD during gestation that might affect the offspring rat neurodevelopment, and that characterization should be further explored in a brain region-specific manner level as well as through the parallel examination of changes in the offspring rat brain lipid composition.